Investigation of tablettability and drug release properties of ethyl cellulose - Gaikwad, Vinod L; Jadhav, Namdeo R (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of the present research is to investigate systematically the tablettability and drug release properties of ethyl cellulose (EC) in compact form. A total of nine batches of compacts containing metformin hydrochloride (MTF) as model drug and ECs with varying viscosity grades (7, 10, and 100 cps) at 10, 20 and 30% w/w contents were prepared. Profound effect of viscosity grades and content of EC on compression behavior of granules and drug release from compacted matrices was observed. An increase in EC 7 cps content resulted improvement in tensile strength and compactibility. However, compression susceptibility gets inversely affected. EC 7 cps has shown MTF release, which is extended upto 10 hours (t90%), attributed to high interparticulate interactions. Similar trend was observed with both EC 10 cps (t90%; upto 13 hours) and 100 cps (t90%; upto 10 hours). Surprising results were observed for matrices of EC 10 cps at 20% w/w, which showed moderate compactibility and tensile strength, but extended the MTF release for maximum time among all compact formulations (t90%; 13 hours; peppas model). These results show the use of EC 10 cps in formulations desired for extended drug release at its optimum content. Matrices containing EC 100 cps have shown better compressibility and compactibility among all batches. The anomalous behavior of high viscosity EC (at 20% w/w content) matrices releasing drug in shorter time (t90%, 8 hours; zero order) can be ascribed to poor matrixing of MTF in EC network due to high molecular weight of EC 100 cps.